Role of IPF genetic risk loci in post-COVID-19 lung abnormalities: a cohort study - James Johnston; Christopher Carlsten; Christopher J Ryerson; Alyson W Wong; Cameron J Hague; Julia Yang; Janice Leung; Daniel-Costin Marinescu; Aditi Shah; Darra Murphy (BMJ Open Respiratory Research)
Introduction Persistent lung abnormalities following COVID-19 infection are common. Similar parenchymal changes are observed in idiopathic pulmonary fibrosis (IPF). We investigated whether common genetic risk factors in IPF are associated with developing lung parenchymal abnormalities following severe COVID-19 disease.Methods Consecutive adults hospitalised for laboratory-confirmed COVID-19 infection were prospectively recruited from March to May 2020. Three single-nucleotide polymorphisms (SNPs) conferring risk for IPF were genotyped (MUC5B rs35705950, ATP11A rs1278769 and DPP9 rs12610495). High-resolution CT and pulmonary function tests were performed at 3 months postdischarge from hospital. Ground glass opacities and reticulation on imaging were visually quantified by two expert thoracic radiologists. Linear regression was used to evaluate the association between risk alleles at each of the three SNPs and (a) lung parenchymal abnormalities as well as (b) pulmonary function, adjusted for age, sex, smoking history and days spent on supplemental oxygen during acute illness.Results 71 patients were included. Mean age was 63±16 years, 62% were male, 31% were ever-smokers and median hospital length of stay was 9±11 days, with 23% requiring mechanical ventilation. The MUC5B risk allele was associated with a significant decrease in ground glass (β=−0.8, 95% CI −1.5 to –0.1, p=0.02) at 3 months, and this finding was paralleled by a concurrent but non-significant trend towards increased diffusion capacity for carbon monoxide (DLCO) (β=8.8, 95% CI −1.2 to 18.8, p=0.08) compared with patients without this risk allele. None of the risk alleles were significantly associated with reticulation at 3 months.Conclusion In an adjusted analysis controlling for severity of infection, MUC5B was associated with reduced ground glass and a trend towards concordant higher DLCO at 3 months after severe COVID-19 illness. This hypothesis-generating result suggests a possible protective effect of MUC5B in postinfectious lung abnormalities as compared with fibrosis in IPF, highlighting a plausible trade-off between its role in immune defence and epithelial cell function.